Guide Dog for Visually Impaired People - Hala Koni; Nasser Aker (Dr. Aladdin Masri, 2026)
This project presents the design and implementation of a multifunctional robot dog intended for both assistance and security applications. The robot is designed to support visually impaired users by providing guided navigation and to perform basic guarding tasks such as monitoring its surroundings and issuing alerts. The system integrates multiple sensors, including LiDAR, a camera, and inertial sensors, along with an audio output system for feedback and alerts. The mechanical structure is based on a quadruped design with servo-driven legs and custom 3D-printed parts made from PLA+. Control and processing tasks are distributed across embedded controllers and a single-board computer to manage movement, sensing, and navigation. Throughout development, several challenges were encountered, including power management, mechanical design, calibration, and component availability. Despite these challenges, the final prototype demonstrates the feasibility of combining guide and guard functionalities in a single robotic platform and provides a strong foundation for future development.
--
The main purpose of this project is to design and implement a robot dog that can perform two main functions: guiding visually impaired individuals and acting as a guard robot for surveillance purposes. The project aims to develop a system that can navigate using LiDAR, and inertial sensors, allowing the robot to move safely and autonomously in indoor and outdoor environments. A camera is used to support visual detection, while a speaker enable basic human robot interaction through voice commands, alerts, and audio feedback. Another objective of this work is to integrate different hardware and software components, including microcontrollers, sensors, communication modules, and actuators, into a single coordinated system. Through this project, the goal is not only to build a functional robotic platform, but also to gain hands-on experience in robotics, embedded systems, sensor integration, and intelligent control, while demonstrating how multiple technologies can work together to solve real-world problems
--
Keywords: Health